INFLUENCE OF STRONG MONSOON-DOMINATED CLIMATE ON BIOGEOCHEMISTRY OF THE HEAVILY ANTHROPOGENIC IMPACTED BRANTAS RIVER ESTUARIES AND MADURA STRAIT COASTAL WATER, EAST JAVA, INDONESIA - Nugrahadi, M.S. (Marine Research in Indonesia, 2011)
Brantas River basin and Madura Strait in East Java Indonesia, are subject to heavily change in land use and land cover, and Brantas River Basin is a very important densely populated area in East Java, Indonesia for agriculture, industry as well as for settlement. The aim of the research is to elucidate the fate of transformation of bio-elements (organic carbon, Nitrogen (N), Phosphorus (P), and Silicate (Si)) and its seasonal variability. The contrast river discharge combined with tide generates the distinctive mixing zone during rainy and dry season. Dissolved Inorganic Nitrogen (DIN) and Dissolved Inorganic Phosphorus (DIP) concentrations in the river are high and decrease to the very low value seaward. N:P ratio has seasonal variation due to large discrepancy of DIN and DIP supply from land to the sea. Dissolved Inorganic Silicate (DSi) in river and estuaries is extremely higher than the average in the world (> 150 mM). Chlorophyll-a (Chl-a) in dry season in the coastal water is higher than the rainy season. Due to high Total Suspended Matter (TSM), the primary production is limited by the light in the coastal water.